Herpes simplex type 2 pneumonia - Calore,Edenilson Eduardo (2002)
Extensive reviews of pulmonary infections in AIDS have reported few herpetic infections. Generally these infections are due to Herpes simplex type 1. Pneumonia due to herpes type 2 is extremely rare. We describe a 40 year-old HIV positive woman who complained of fever, cough and dyspnea for seven years. She had signs of heart failure and the appearance of her genital vesicles was highly suggestive of genital herpes. Echocardiography showed marked pulmonary hypertension, right ventricular hypertrophy and tricuspid insufficiency. After a few days of hospitalization she was treated with Aciclovir and later with Ganciclovir. An open pulmonary biopsy revealed an interstitial inflammation, localized in the alveolar walls. Some pulmonary arteries had widened walls and focal hyaline degeneration. Immunohistochemistry indicated that the nuclei had herpes simplex virus type 2 in many endothelial cells (including vessels with widened walls), macrophages in the alveolar septa and pneumocytes. There was clinical improvement after treatment for herpes. We concluded that as a consequence of herpes infection, endothelial involvement and interstitial inflammation supervene, with thickening of vascular walls and partial obliteration of the vessel lumen. A direct consequence of these changes in pulmonary vasculature was pulmonary hypertension followed by heart failure.